Efectos en el tracto reproductivo, digestivo y pérdida de peso corporal del ave semipesada sometida a descanso ovárico (2010)
ABSTRACT: The effects on the reproductive and digestive tract and loss of body weight of the Brown egg layers submitted to ovarian rest. This research evaluated the application of the ovarian rest (OR) on brown egg layers and the effect the age and duration of feed withdrawal have over the reproductive and gastrointestinal tract. 840 Hy-Line Brown ® layers were used at 64 weeks of age in which three ages of induction to the OR (65.70 and 75 weeks) and three feed withdrawal periods (five, ten and fifteen days) in a completely randomized statistical model, nested, of balanced and fixed effect. Sacrifices were carried out in order to evaluate body weight, weight of the digestive and reproductive tract (ovary and oviduct), follicle percentage with a diameter equal to or higher than ten mm (LYF) and the percentage of the bird’s weight loss. The model was significant (p<0.05) for all the variables evaluated; the age presented a significant effect (p<0.05) over the ovary weight and the follicle percentage (LYF), while the duration of the feed withdrawal related to the age had a significant effect (p<0.05) on all the variables, which indicates a greater effect of the feed withdrawal period contrasted to the age of the application of the OR upon the variables evaluated. The ovary’s weight (age 65:15.87 to ± 15.11; age 70: 7.92b ± 5.46; and age 75: 7.54b ± 4.96) and the follicle percentage (65: 43.75 to ± 21.54; age 70 18.05b ± 8.72 and age 75: 8.33b ± 6.85) showed a lowering tendency as the age increased. This type of behavior is associated with the gradual decrease in the number of follicles and the extended time between the maturation of one follicular wave and the next as the layer ages (Kim, Donalson, 2006; North, Bell, 1990). The weight loss percentages (age 65: 24.24 ± 8.53%; age 70: 20.91 ± 5.50% and age 75: 20.88 ± 7.15%) were low compared to the reports on white egg layers, possibly due to the content of lipidic reserves which offers the brown egg layers the capacity to tolerate feed withdrawal minimizing the effect over weight loss. All three ages had a direct relation between the extent of the feed withdrawal periods and the effect over reproductive atrophy and weight loss The latter leads to the conclusion that periods of feed withdrawal over 10 days are not necessary due to the fact that the weight loss and reproductive atrophy needed in the implementation of the OR is achieved.